UPAYA MENINGKATKAN KETERAMPILAN KOLABORASI DAN HASIL BELAJAR PESERTA DIDIK KELAS IVA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DI SDN SN KEBUN BUNGA 4 BANJARMASIN - Rahayu, Isnaniah; Rahimah; Rahmatina, Rina; Yusniarti; Fazriah, Nurul; Rachman, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem identified in this study was the low level of students' collaboration skills and Mathematics learning outcomes among fourth-grade students at SDN SN Kebun Bunga 4 Banjarmasin. Students were less actively involved in learning activities, experienced difficulties in working collaboratively, and had not yet achieved the predetermined learning mastery criteria. This study aimed to improve students' collaboration skills and learning outcomes through the implementation of the Problem Based Learning (PBL) model. The study employed Classroom Action Research (CAR) conducted in three meetings. The subjects were 24 students of class IVA, consisting of 13 male and 11 female students. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative and qualitative methods. The results showed an improvement in students' collaboration skills and learning outcomes. Collaboration skills increased from 42% in the first meeting to 75% in the second meeting and 88% in the third meeting. Similarly, learning outcomes increased from 46% in the first meeting to 66% in the second meeting and 87.50% in the third meeting. Therefore, the implementation of the Problem Based Learning model improved students' collaboration skills and Mathematics learning outcomes.